PENGARUH STRATEGI PEMASARAN TERHADAP PENYEWAAN TENDA CAMPING PADA CV SHELTER ADVENTURE RIAU PEKANBARU - Khornelis Dehotman (Eko dan Bisnis: Riau Economic and Business Review, 2026)
Abstract : The purpose of this study was to determine the effect of marketing strategy on camping tent rentals at CV. Shelter Adventure Riau Pekanbaru. The population in this study was 873 consumers, and the research sample was 90 consumers. The research method used was descriptive with a quantitative approach. The average score for all statements regarding marketing strategy was 4.76, meaning respondents strongly agreed with statements about marketing strategy. Meanwhile, respondents' average score for statements about rentals was 4.39, meaning they strongly agreed. The data analysis used is simple linear regression with the regression results obtained, namely Y = 18.290 + 0.646X which has a positive relationship direction, namely if the marketing strategy variable increases, then the rental variable will increase. Based on the results of the t test, it was obtained that the t count value was 11.091> t table 1.98729 with a significance level of 0.000 <0.05. This means that the marketing strategy has a positive and significant effect on the marketing strategy for camping tent rentals at CV. Shelter Adventure Riau Pekanbaru. The R Square value of 0.583 or 58,3% means that the Training variable has an influence on camping tent rentals of 58,3%.